Income Taxation and Its Family Components in France and Germany: A Comparison of Distributional Effects - Katharina Wrohlich; Fabien Dell; Alexandre Baclet (Weekly Report, 2005)
A comparison based on German and French micro data shows that the redistributive effects of family support provided in the form of tax relief are stronger in Germany than in France. This is true both for redistribution between households of different sizes and for redistribution between households with different incomes. The average burden on single individuals without children compared to other types of household is larger in Germany than in France. Couples with one, two, or three children bear a comparatively lower burden in Germany than in France. For couples with four or more children, the relative income-tax burden is the same in the two countries. Overall, all German households with children bear a below-average share of the income-tax burden, while in France this applies only to lone parents and to couples with three or more children. In France, therefore, there is a greater degree of redistribution than in Germany from households consisting of couples with one or two children to households that have three or more children. The study also revealed differences in the redistributive effects related to the amount of household income. In all households with children, the burden is much lower (or the relief obtained is much higher) in the bottom five deciles in Germany than in France. Only couples with children who are in the top two deciles (or in the top three deciles in the case of couples with three children) enjoy greater relief under the French system than their counterparts in Germany. For a long time, family policy has been more of a peripheral question in the political debate in Germany, but issues relating to family policy have recently been gaining increasing priority. One important reason is the fact that family policy in Germany - despite the substantial amount of public funds spent on it compared to other countries - performs less well with respect to a range of indicators than the family policy of other European countries. Indicators that deserve particular mention in this respect are the low birthrate and the low share of working mothers. Contributors to the public debate often cite France, whose income-tax system and supply of state-funded child-care facilities are believed to be particularly supportive of families. France is seen as an example of a country with a 'successful family policy' because both its fertility rate and the share of working mothers in its labor force are higher than in Germany and, in particular, because childlessness is less common there amongst highly qualified women than in Germany. 4 French family policy differs from German family policy in many respects, ranging from the supply of subsidized child-care facilities and the design of the regulations on parental leave benefits to the family policy components of the income-tax system.5 The focal point of this report is a comparison between the redistributive effects engendered in Germany and France by the different tax treatment of families with children. The German instruments concerned are child benefits (Kindergeld) and the tax-free allowance for dependent children (Kinderfreibetrag); the French measures are the 'family splitting' procedure in the calculation of income tax and family allowances (Allocations Familiales). If a comparison of the relief provided by these measures is to yield useful information, then it must, on principle, also take account of the empirical income distribution and of the different definitions of taxable income. This is particularly important in the context of a Franco-German comparison because there are some substantial differences in the definitions of taxable income used in the two countries. Having compared the tax treatment of families in France and Germany, the results of the empirical analysis of the effective average tax burden or amount of tax relief will then be presented; the analysis is based on the year 2001 because more recent data are not yet available for France.
Keywords: 330